Effects of Different Roughage Diets on Fattening Performance, Meat Quality, Fatty Acid Composition, and Rumen Microbe in Steers - Zhu, Xiaoyan; Liu, Boshuai; Xiao, Junnan; Guo, Ming; Zhao, Shumin; Hu, Menglin; Cui, Yalei; Li, Defeng; Wang, Chengzhang; Ma, Sen; Shi, Yinghua (Frontiers in Nutrition, 2022)
This study aimed to evaluate different roughages on fatting performance, muscle fatty acids, rumen fermentation and rumen microbes of steers. Seventy-five Simmental crossbred steers were randomly divided into wheat straw group (WG), peanut vine group (PG) and alfalfa hay group (AG), with 5 replicates of 5 steers each. The results showed a highest average daily gain and lowest feed/gain ratio in AG group (P = 0.001). Steers fed alfalfa hay had the highest muscle marbling score and n-3 polyunsaturated fatty acid (PUFA), and also the rumen NH3-N and microbial protein (MCP) concentration among the three groups (P < 0.05). Correlation analysis showed that ruminal NH3-N and MCP were negatively correlated with muscle saturated fatty acid (SFA), while ruminal MCP was positively correlated with muscle PUFA and n-3 PUFA (P < 0.05). 16S rRNA analysis indicated that fed alfalfa hay decreased the abundance of Ruminococcaceae_UCG-001(P = 0.005). More importantly, muscle SFA deposition were positively correlated to the abundance of Ruminococcaceae_UCG-001 (P < 0.05), while the muscle PUFA and n-3 PUFA deposition were negatively correlated to it (P < 0.01). Therefore, alfalfa hay provides a better fattening effect on steers. Alfalfa rich in n-3 PUFA would reduce the abundance of Ruminococcaceae_UCG-001 involved in hydrogenation, increase the rumen protective effect of C18:3 n−3, which is beneficial to the deposition of muscle n-3 PUFA and PUFA.